1989
DOI: 10.7164/antibiotics.42.788
|View full text |Cite
|
Sign up to set email alerts
|

In vitro immunosuppressive properties of spergualins to murine T cell response.

Abstract: Deoxyspergualin has strong immunosuppressive activity in animals. However, it shows less in vitro immunosuppressive activity at the therapeutic concentration used for in vivo administration. Recently, we reported that there are sometechnical problems with in vitro experiments. In this report, the effects of spergualins were examined under in vitro conditions which excluded these problems, and compared with cyclosporine A (CYA). Spergualins have suppressive effects on mixed lymphocyte response (MLR)and cytotoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 12 publications
2
16
0
Order By: Relevance
“…1). However, no decrease in in vitro IL-2 production was observed in the treated animals, in accordance with other reports [9][10][11]. In contrast, the IL-2 levels in animals treated with lower doses of DSP such as 0.6 and 1.5 mg/kg was significantly higher than the control level ( fig.…”
Section: Resultssupporting
confidence: 77%
“…1). However, no decrease in in vitro IL-2 production was observed in the treated animals, in accordance with other reports [9][10][11]. In contrast, the IL-2 levels in animals treated with lower doses of DSP such as 0.6 and 1.5 mg/kg was significantly higher than the control level ( fig.…”
Section: Resultssupporting
confidence: 77%
“…Concerning the activation of autoreactive lymphocytes, the beneficial effect of LF 15-0195 may be due to a direct effect of this drug on T cell activation or to an indirect effect by interfering with APC functions. It has been shown that DSG inhibits the T cell proliferation induced by T cell mitogens or alloantigens (34,35) and the generation of secondary CTLs (36). Furthermore, DSG inhibits Agspecific T cell proliferation at the level of the Ag-presenting monocytes by interfering with the capacity of these cells to process and present Ags (37).…”
Section: Discussionmentioning
confidence: 99%
“…The ability of an immunosuppressant to prevent donor species presensitization and coincidentally induce short-term species specific tolerance was first described with deoxyspergualin (9) and ascribed at the time to a direct B cell inhibition. However, it is now recognized that the manifold actions of DSG include potent T-cell suppression (38,39).…”
Section: Discussionmentioning
confidence: 99%